Association of allostatic load measured by allostatic load index on physical performance and psychological responses during arduous military training - Evan D. Feigel; Kristen J. Koltun; Mita Lovalekar; Christopher K. Kargl; Matthew B. Bird; Jennifer N. Forse; Varun J. Patel; Brian J. Martin; Elizabeth F. Nagle; Karl E. Friedl; Bradley C. Nindl (Physiological Reports)
Abstract Military personnel experience decrements in physical fitness and psychological well‐being during training that may be attributed to allostatic load. This investigation examined the association between allostatic load measured by the allostatic load index (ALI) and physical performance and psychological responses in personnel undergoing a 10‐week training course. Thirty‐one participants (14 women) provided biochemical, questionnaire (perceived stress appraisal (PSS), sleep difficulty (SD), resilience (CD‐RISC‐25), and Physical Fitness Test (PFT; three‐mile run [3MR], pullups, Run‐Row PFT score, Push‐Pull PFT score, Crunches‐Plank PFT score, and total PFT score)) data before and after training. ALI (0–8) was calculated using biomarker components from neuroendocrine, autonomic, and immune systems. Simple linear regression analysis assessed the association between change (Δ) in ALI and responses. Backward stepwise regression identified components associated with responses (α = 0.05). In men, ΔALI was associated with Δpullups (β = −0.88, p = 0.015), Δpush‐pull PFT score (β = −2.87, p = 0.013), Δtotal PFT score (β = −3.48, p = 0.007), and ΔSD (β = −0.56, p = 0.046) with immune components explaining relationships. In women, ΔALI was associated with ΔSD (β = −1.25, p < 0.001) and ΔCD‐RISC‐25 (β = 2.65, p = 0.025) with no component explaining relationships. Increased ALI is associated with worsened physical performance in men and improved psychological outcomes in women, highlighting potential sex‐specific responses to increased allostatic load during training.